Sorção de selênio em solos do bioma cerrado - Abreu, Lívia Botelho de (2011)
The study of Se distribution in soils is of general interest because of the narrow range between deficiency and toxicity. The chemical species of Se with the greatest toxicological potential is selenate, due to its high mobility in soils. The study of selenate chemistry is of great importance to understand Se behavior in tropical soils. A batch adsorption experiment was performed using 2 g soil samples in 20 mL of solution with 10 different Se concentrations in the form of Na2SeO4, for 24 h, with a background electrolyte (0.03 mol L-1 NaNO3). The adsorption velocity was tested under the same experimental conditions, but only at the concentration of 1 mg L-1 Se. The shaking time ranged from 15 min to 72 h. The Freundlich adsorption isotherms fit well to the experimental data. For the adsorption velocity study, the best model was the pseudo-second order, and the time required to reach equilibrium was about 4 hours. In general, the Kd values were low and Se tended to be more in solution than in the solid phase. The most weathered soils, with higher clay and Al and Fe oxide contents also had the highest affinity for Se. In sandy and loamy soils, Se tends to be less adsorbed and can therefore be taken up by plants or easily leached, damaging the ecosystem.